Faktor-Faktor yang Berhubungan dengan Frekuensi Pemeriksaan Kehamilan di Puskesmas Teluk Kijing Tahun 2024 - Erika Lemestri; Intan Sari; Wahyu Ernawati; Putu Lusita Nati Indriani (JURNAL KEBIDANAN AKADEMI KEBIDANAN BUDI MULIA PALEMBANG, 2024)
To reduce MMR in Indonesia, one of the efforts that can be made is to implement a health program for pregnant women in the form of Antenatal Care (ANC). Antenatal Care (pregnancy check-ups) aims to recognize and identify problems so that pregnancy health can be maintained, so that the mother and child are in the best possible condition at the time of delivery. The study aims to Factors Related to the Frequency of Pregnancy Check-ups at Teluk Kijing Public Health Center in 2024. This study design uses an analytical survey with a cross-sectional method. The population in this study were all pregnant women in the third trimester who checked their pregnancy in the work area of ​​Teluk Kijing Health Center, Musi Banyuasin Regency from January to December 2023, totaling 350 pregnant women. The sampling technique in this study was accidental sampling, namely samples were taken from respondents who happened to come to Teluk Kijing Health Center when the study was conducted. The analysis technique used Univariate, Bivariate (Chi square). Based on the results of the Chi Square statistical test, there was a partial relationship between economic status and the frequency of pregnancy check-ups at Teluk Kijing Health Center in 2024, the results obtained a p value = 0.002, there was a partial relationship between education and the frequency of pregnancy check-ups at Teluk Kijing Health Center in 2024, the results obtained a p value = 0.001, there was a partial relationship between knowledge and the frequency of pregnancy check-ups at Teluk Kijing Health Center in 2024, the results obtained a p value = 0.004. It is expected that the results of this study can be a picture for the health center to further improve health services, especially pregnancy examination services